Investigation of electromyography of major muscle groups while hiking out during sailing on both land and water - Tan, C. C. R.; Toh, J. Y.; Liao, K.; Xie, W. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study is to compare the Electromyographic (EMG) readings of muscle activation while hiking out on both land and water. This preliminary study aims to determine if there is a significant difference between EMG readings conducted in laboratory conditions as well as on water when the subject is hiking out while sailing. Muscle groups tested in this study were the Rectus Femoris, Vastus Laterialis and the Tibialis Anterior. EMG readings were taken and expressed as a percentage of the maximal voluntary contraction (MVC) baseline from the subject. The preliminary results of this study show that the RF muscles contribute more to hiking out than the VL muscles in the laboratory and at sea.